Medieval Neoplatonism in Borges - Magnavacca, Silvia (Anales del Seminario de Historia de la Filosofía, 2007)
This paper is divided into three parts. In the first part, the A. describes Borges’ particular concern about medieval philosophy as a reader. In the second and larger part, she refers to medieval neoplatonism main notes and claims that the argentine writer applied echoes of those notes to the development of his own literature. In this sense, Scotus Erigena and Nicholas Cusanus’thesis are specially quoted. Lastly, the A. suggests that, in spite of the use of medieval neoplatonism in his poems and essays, Borges was skeptical about it as a philosophical point of view.